S37 The effect of asthma management plans and annual asthma reviews on exacerbations. (12th November 2019) - Naqvi, S; Patel, R; Bhullar, K; Quint, JK; Bloom, CI
Abstract : Introduction and aims: This study aimed to evaluate the effect of two different non-pharmacological interventions (asthma management plan and annual asthma review) on asthma exacerbations, one year after the intervention. This investigation expands upon existing studies which analyse other risk factors associated with exacerbations in a UK asthma population. Methods: Clinical Practice Research Datalink and Hospital Episode Statistics data from January 2004 to January 2017 were used to identify a nationally-representative asthma population. Patients were included that had at least two years of follow-up. The presence of the two main exposures were measured in the first year: annual asthma review and asthma management plan. The risk of an exacerbation in the following year was then calculated using a multivariate logistic regression model. The following variables were included in the model: gender, age, BMI, asthma severity (BTS step), smoking history, atopy, gastro-oesophageal reflux disease (GORD), anxiety, depression and exacerbations in the year prior to study entry. Results: Of the 370, 528 eligible patients, 110, 467 (29.81%) received an annual asthma review, whilst only 23, 140 (6.25%) were given an asthma management plan. Presence of an asthma management plan or an annual review did not increase the odds of an exacerbation (management plan: adjusted OR=1.03, 95% CI 1.00–1.07, p>0.05; annual review: adjusted OR=1.01, 95% CI 1.00–1.03, p>0.05; table 1). Of the confounders adjusted for, increasing asthma severity and history of exacerbations in the year prior to study entry had the greatest effect on the exacerbation odds, increasing by 24.99±2.56 and 7.19±0.15 respectively. Conclusions: One year post-study entry, presence of either intervention was found not to have any significant association with exacerbations. This study therefore suggests that these non-pharmacological interventions did not reduce the risk of exacerbations; however, it is possible that there were other confounders that were unaccounted for. Further studies investigating the type of management plan (verbal or written), compliance with plans and different interventions such as inhaler technique checks would be useful.